2015
DOI: 10.1007/s00436-015-4615-8
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of a novel cysteine-rich antimicrobial peptide from the salivary glands of the tick Rhipicephalus haemaphysaloides

Abstract: Ticks encounter various microbes while sucking blood from an infected host and carrying these pathogens in themselves. Ticks can then transmit these pathogens to vertebrate hosts. The immune system of ticks can be stimulated to produce many bioactive molecules during feeding and pathogen invasion. Antimicrobial peptides (AMPs) are key effector molecules of a tick's immune response, as they can kill invading pathogenic microorganisms. In this study, we identified a novel cysteine-rich AMP, designated Rhamp1, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Recently, carbohydrate metabolic compensation and peroxiredoxin production were reported to be necessary to maintain the redox balance in ticks ( Kusakisako et al, 2016 ; Della Noce et al, 2019 ). It has been proposed that tick microbiome would be influenced by oxidative stress ( Narasimhan and Fikrig, 2015 ), and different AMP would have different inhibitory consequence on microbial growth ( Saito et al, 2009 ; Zhang et al, 2015 ). These immune responses in ticks may work together and eventually influence the viral and bacterial composition of a specific host blood meal through a complicated pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, carbohydrate metabolic compensation and peroxiredoxin production were reported to be necessary to maintain the redox balance in ticks ( Kusakisako et al, 2016 ; Della Noce et al, 2019 ). It has been proposed that tick microbiome would be influenced by oxidative stress ( Narasimhan and Fikrig, 2015 ), and different AMP would have different inhibitory consequence on microbial growth ( Saito et al, 2009 ; Zhang et al, 2015 ). These immune responses in ticks may work together and eventually influence the viral and bacterial composition of a specific host blood meal through a complicated pathway.…”
Section: Discussionmentioning
confidence: 99%
“…PIXR might influence the tick gut microbiome composition by regulating the ability of gram-positive bacteria to form biofilms in the gut when the tick takes a blood meal ( Narasimhan et al, 2017 ). These alterations may influence B. burgdorferi entering the tick gut in multiple ways ( Zhang et al, 2015 ). We identified that the gene encoding a protein similar to PIXR was upregulated in the fully fed I. persulcatus ticks; however, its role in the transmission of Borrelia and other tick-borne pathogens deserves further study.…”
Section: Discussionmentioning
confidence: 99%